Reviewing Islamic Criminal Punishment Views On Corruption Asset Confirmation Without Crimination - Mustaufiq, Mustaufiq; Kurniati, Kurniati; Misbahuddin, Misbahuddin (Institut Agama Islam Negeri (IAIN) Kendari, 2023)
The paper discusses the Islamic criminal system's views on confiscating corruptors’ assets, which has been proposed for a draft law since 2012. The confiscation of assets is a solution to provide a deterrent effect and restore state losses. This study uses library research methods with a normative approach to answering the question,